Root canal treatment of mandibular first premolar with Vertucci class VIII configuration: A case report - Lukman, Siti R.; Nugroho, Juni J. (Journal of Case Reports in Dental Medicine, 2025)
Introduction: The mandibular first premolars usually have a single root canal, with the presentation of root canal variations being quite rare. Mandibular first premolars with three root canals are very rare. The anomaly occurs during the tooth development phase, causing anatomical variations. Complex root morphology poses a challenge to the dentist in performing treatment. A good and thorough knowledge of the morphology and possible root canal variations can help to obtain adequate treatment.Case Report: A 21-year-old male with a complained of pain in the area of the lower right posterior tooth, accompanied by discomfort when biting about 3 months ago. Objective examination revealed caries on the disto-oclusal of the lower right first premolar. Vitality, percussion, and palpation tests were negative. Periapical radiographs showed a radiolucent area in the disto-oclusal region that had reached the pulp, the number of root canals was 3 and radiolucent in the apical lingual root. The diagnosis for tooth 44 was asymptomatic irreversible pulpitis with asymptomatic apical periodontitis. The root canal configuration was determined to be Vertucci class VIII. Root canal treatment using rotary crown down preparation technique and obturation with warm vertical compaction, class II composite resin restoration.Discussion: Vertucci class VIII is a rare root canal configuration. Successful treatment of complex root canals can be supported by proper radiographic interpretation, understanding of root canal anatomy, adequate preparation, medicament and obturation techniques.Conclusion: Root canal treatment of mandibular first premolars with Vertucci class VIII configuration using warm vertical compaction obturation technique showed good results.